Association of handgrip strength and/or walking pace with incident chronic kidney disease: A UK biobank observational study. Issue 2 (28th January 2023) - He, Panpan; Ye, Ziliang; Liu, Mengyi; Li, Huan; Zhang, Yuanyuan; Zhou, Chun; Wu, Qimeng; Zhang, Yanjun; Yang, Sisi; Liu, Chengzhang; Qin, Xianhui
Abstract: Background: The individual and combined relations of handgrip strength and walking pace with the risk of chronic kidney disease (CKD) remain uncertain. We aimed to investigate the relationship of handgrip strength and/or walking pace with incident CKD, using data from the large‐scale, observational UK Biobank. Methods: A total of 417 504 participants free of prior kidney diseases were included from UK Biobank. Handgrip strength was assessed by dynamometer. The walking pace was self‐reported as slow, average, or brisk. Cox proportional hazards models were applied to calculate hazard ratios (HRs) and 95% confidence intervals (CIs) for incident CKD. Results: The average age of the study population was 56.3 (SD, 8.1) years. 192 012 (46.0%) of the participants were male. The mean handgrip strength was 23.5 (SD, 6.2) and 40.0 (SD, 8.8) kg for females and males, respectively. Over a median follow‐up duration of 12.1 years, 11 064 (2.7%) participants developed incident CKD. Handgrip strength was significantly inversely associated with the risk of incident CKD in both males and females (both P for trend <0.001). When handgrip strength was assessed as sex‐specific quartiles, compared with those in the first quartile, the adjusted HRs (95% CI) of incident CKD in participants in the second, third and fourth quartiles were 0.84 (0.79, 0.89), 0.76 (0.71, 0.81) and 0.72 (0.67, 0.77), respectively. Compared with those with slow walking pace, participants with average (HR, 0.64; 95% CI: 0.60–0.68) or brisk (HR, 0.53; 95% CI: 0.49–0.57) walking pace had significantly lower risks of incident CKD. Compared with those with both lower handgrip strength (the first quartile) and slow walking pace, the lowest risk of incident CKD was observed in participants with both higher handgrip strength (the 2–4 quartiles) and average or brisk walking pace (HR, 0.51; 95% CI: 0.46–0.55). Conclusions: Handgrip strength and walking pace were significantly inversely associated with incident CKD in the general population.